2023
DOI: 10.1002/ejic.202300005
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Metalloporphyrin‐Based Electrochemical Sensing Applications: From Small Gasotransmitters to Macromolecules

Abstract: At the beginning of his youthful sixth decade, this work is dedicated to Prof. Dr. Fabio Doctorovich. He is distinctive in organometallic chemistry. During his successful career, he has been studying the reactivity and application of metalloporphyrins. Metalloporphyrins are organometallic complexes that exhibit, through synthetic modifications, the ability to tune their optical and electrochemical properties and their selectivity towards a particular molecule or ion. For this reason, they are systems extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 202 publications
(337 reference statements)
0
3
0
Order By: Relevance
“…Generally, for application in sensors (due to synthetic and supramolecular reasons, for example to make additional interaction points, etc. ), porphyrins with some peripheral substituents (often it is phenyl or naphthyl rings in meso positions) are conventionally used [10,12,24,87–90] . These substituents can prevent free rotation of a guest by creation of steric hindrance or formation of additional non‐covalent bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, for application in sensors (due to synthetic and supramolecular reasons, for example to make additional interaction points, etc. ), porphyrins with some peripheral substituents (often it is phenyl or naphthyl rings in meso positions) are conventionally used [10,12,24,87–90] . These substituents can prevent free rotation of a guest by creation of steric hindrance or formation of additional non‐covalent bonds.…”
Section: Resultsmentioning
confidence: 99%
“…), porphyrins with some peripheral substituents (often it is phenyl or naphthyl rings in meso positions) are conventionally used. [10,12,24,[87][88][89][90] These substituents can prevent free rotation of a guest by creation of steric hindrance or formation of additional non-covalent bonds. The latter occurs when substituents have additional functional groups, like OH, NH 2 , COOH, etc., which are able to make noncovalent bonds with a guest to form a supramolecule.…”
Section: Aromatic Peripheral Substituents On Porphyrinmentioning
confidence: 99%
“…In recent work, the reaction between NO * and thiols has been studied with the main objective of evaluating whether HNO is a reaction intermediate. Our analysis focused on the reactions of NO * with 1-hexanethiol (R 6 SH), cysteine (Cys), benzenethiol (PhÀ SH), and benzeneselenol (PhÀ SeH), using Mn(III) 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrinate (Mn(III)TCPP) as a scavenger for HNO, [95] an HNOselective electrode, [96][97][98] and ab initio methods. The results revealed that the reaction is first order in both reagents and that the HNO production rate varies in the following order: PhÀ SeH > PhÀ SH @ R 6 À SH > Cys.…”
Section: Reaction Of No * With Thiolsmentioning
confidence: 99%